Silver economy and entrepreneurship, an emerging innovative area: An academic, scientific and business framework for building new knowledge - Álvarez Diez, Rubén Carlos; Vega Esparza, Reina Margarita; Bañuelos-García, Víctor Hugo; Villegas Santillán, María Teresa; Llamas Félix, Blanca Isabel; Arredondo Luna, Verónica; Hernández Ponce, José Rogelio; García Martínez, Flor de María; Alvarado-Peña, Lisandro José; López-Robles, José Ricardo (Iberoamerican Journal of Science Measurement and Communication, 2022)
Objective. Identify and describe the main research, development and innovation topics, agents and most relevant articles on the silver economy and entrepreneurship. Design/Methodology/Approach. A combination of bibliometric techniques, tools and methodologies was applied to analyze the performance, impact and scientific mapping of publications and authors using the VOSviewer software. In the first instance, the performance and impact analysis allowed us to understand the qualitative part of the knowledge area. In this sense, the main authors, organizations, countries, sources of information and areas of knowledge were identified. This qualitative analysis has been covered through three maps of science, the first of which described the main themes, followed by evolution and closing with the relationship between the authors of said publications. Finally, the results were jointly analyzed, and a reference framework was established. Results/Discussion. The conjunction between the silver economy and entrepreneurship is giving rise to a new area of knowledge, in which it seeks to promote the development of society as a whole, attending, on the one hand, to the economy linked to the adult population and, on the other hand, to the entrepreneurship of said age group, as well as to all those agents that integrally promote entrepreneurship. Although this new area of knowledge is at an early stage, it is already possible to identify four main development clusters: Silver Entrepreneurship; Entrepreneurship strategies; New business models; and Aging of the population, which reinforce the above and mark a vertical vision, but complementary to other areas of knowledge. Conclusions. With the growing population of older adults in the world and the trend in the same direction of economic and social changes, pension systems and others no less important such as health, as well as the prevailing need to design public policies that allow adequate development of older people, have generated interest in researchers who propose and study aspects that will enable us to know the phenomenon in which we are immersed. In this line, entrepreneurship from the perspective of the adult population or silver entrepreneurship is presented as an opportunity to respond to these challenges from perspectives such as research, development and innovation. Originality/Value. A reference framework is established between the silver economy and entrepreneurship to identify the main lines of research, development and innovation and the opportunities and challenges faced by the academic, scientific, technological, social, business communities, and politics.